Pengetahuan Prosedural dan Korelasinya dengan Pengetahuan Konseptual Mahasiswa pada Topik Genetika Populasi Berbasis Molekuler - Murni, Dewi Murni; Amelia, Evi; Lestari, Ling Dwi; Suryaningsih, Septionita; Indriyani, Riza; Zahra, Intan Az (Bioedusiana: Jurnal Pendidikan Biologi, 2024)
Procedural knowledge is one dimension of knowledge that has an important role, which is to help students acquire conceptual knowledge. Procedural knowledge helps students understand concepts in the Genetics Course, including "Molecular-Based Population Genetics." This topic discusses the molecular structure and function of DNA markers in population genetics research and the procedures carried out by scientists in conducting molecular-based population genetics research. This study aims to describe students' procedural and conceptual knowledge of molecular-based Population Genetics and analyze these variables' correlations. This study used a quantitative descriptive research method with Pearson Product Moment correlational design. The study sample amounted to 101 randomly selected students. The collection of student procedural knowledge data is carried out using test techniques. Test questions are essay questions developed based on students' procedural knowledge parameters. Students' conceptual knowledge is measured using short-fill, actual false, and essay questions. Data analysis was performed using correlational descriptive analysis using the SPSS program. Students' procedural and conceptual knowledge are in the deficient category. Students' procedural and conceptual knowledge has a reasonably strong positive correlation. Procedural knowledge contributes to students' conceptual knowledge with a determination score of 21.3%. Based on these findings, lecturers must create a learning process that empowers students' procedural knowledge to improve conceptual knowledge, ultimately improving learning outcomes in the Genetics course.